دخول المذهب المالكي إلى الجزائر (النشأة والتطور) - أمير, فوزي (جامعة الوادي - University of Eloued, 2020)
كثيرا ما يتناول العلماء فترة ظهور المذهب المالكي وانتشاره في ربوع المغرب العربي، والملاحظ في كتاباتهم أنّ النشاط الفقهي المالكي اقتصر على المغرب الأدنى خاصة القيروان، والمغرب الأقصى عموما، ولا نكاد نسمع عن المغرب الأوسط شيئا، وكان هذا الأمر هو المحفز للبحث في هذا الموضوع والكشف عن غموضه، فتناولت الورقات مرحلة دخول الإسلام إلى الجزائر، ثم مرحلة نشأة وانتشار المذهب، وبعدها مرحلة التطور، مع الترجمة لبعض علماء المذهب في الجزائر في المرحلتين. In the literature, Researchers often address the period of the emergence and the spread of the Maliki Doctrine in the Arab Maghreb, and it is clearly well noted in their writings and their works that the Maliki juristic activity was limited to the Near Maghreb Doctrine, in particular Kairouan, For the best of our knowledge, there are no research works dealing with Middle Maghreb Doctrine. The main aim of this research is to present a contribution in the Maghreb Doctrine topic .This work is structured as follows: We begin by studying the period of Islam entering Algeria. Then, we investigate the Period of Formation and Spread of the Doctrine. Finally, we study the Period of Development, by presenting translation for some researchers of the Algerian Doctrine in the two last periods.
Maliki Doctrine To Enter Algeria )origination And Evolution(
مقال في مجلة الشهاب بجامعة الوادي
Keywords: المذهب المالكي، الفقهي، المغرب الأوسط، النشأة، التطور; The Maliki Doctrine, Juristic, Central Maghreb, Origination, Evolution